At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Certainly! Let's consider an explicit function [tex]\( I(t) \)[/tex] where the function describes the value at time [tex]\( t \)[/tex] in terms of the value at time [tex]\( t-1 \)[/tex].
Given the function in an exponential growth form, it can be expressed recursively. Here's how you can express it:
1. Recursive form:
[tex]\[ I(t) = r \cdot I(t-1) \][/tex]
2. Initial condition:
[tex]\[ I(0) = I_0 \][/tex]
Where:
- [tex]\( I(t) \)[/tex] is the value at time [tex]\( t \)[/tex].
- [tex]\( r \)[/tex] is the growth rate.
- [tex]\( I_0 \)[/tex] is the initial value at time [tex]\( t=0 \)[/tex].
Let’s break down the recursive relationship:
- At [tex]\( t = 0 \)[/tex]:
[tex]\[ I(0) = I_0 \][/tex]
This is the initial value of the function.
- At [tex]\( t = 1 \)[/tex]:
[tex]\[ I(1) = r \cdot I(0) \][/tex]
- At [tex]\( t = 2 \)[/tex]:
[tex]\[ I(2) = r \cdot I(1) \][/tex]
Substituting [tex]\( I(1) \)[/tex] from the previous step:
[tex]\[ I(2) = r \cdot (r \cdot I(0)) = r^2 \cdot I_0 \][/tex]
- At [tex]\( t = 3 \)[/tex]:
[tex]\[ I(3) = r \cdot I(2) \][/tex]
Substituting [tex]\( I(2) \)[/tex] from the previous step:
[tex]\[ I(3) = r \cdot (r^2 \cdot I_0) = r^3 \cdot I_0 \][/tex]
Continuing this pattern, at time [tex]\( t \)[/tex], the value can be expressed as:
[tex]\[ I(t) = r^t \cdot I_0 \][/tex]
Thus, this recursive system, with its initial condition, completely describes the explicit form of the function [tex]\( I(t) \)[/tex].
Given the function in an exponential growth form, it can be expressed recursively. Here's how you can express it:
1. Recursive form:
[tex]\[ I(t) = r \cdot I(t-1) \][/tex]
2. Initial condition:
[tex]\[ I(0) = I_0 \][/tex]
Where:
- [tex]\( I(t) \)[/tex] is the value at time [tex]\( t \)[/tex].
- [tex]\( r \)[/tex] is the growth rate.
- [tex]\( I_0 \)[/tex] is the initial value at time [tex]\( t=0 \)[/tex].
Let’s break down the recursive relationship:
- At [tex]\( t = 0 \)[/tex]:
[tex]\[ I(0) = I_0 \][/tex]
This is the initial value of the function.
- At [tex]\( t = 1 \)[/tex]:
[tex]\[ I(1) = r \cdot I(0) \][/tex]
- At [tex]\( t = 2 \)[/tex]:
[tex]\[ I(2) = r \cdot I(1) \][/tex]
Substituting [tex]\( I(1) \)[/tex] from the previous step:
[tex]\[ I(2) = r \cdot (r \cdot I(0)) = r^2 \cdot I_0 \][/tex]
- At [tex]\( t = 3 \)[/tex]:
[tex]\[ I(3) = r \cdot I(2) \][/tex]
Substituting [tex]\( I(2) \)[/tex] from the previous step:
[tex]\[ I(3) = r \cdot (r^2 \cdot I_0) = r^3 \cdot I_0 \][/tex]
Continuing this pattern, at time [tex]\( t \)[/tex], the value can be expressed as:
[tex]\[ I(t) = r^t \cdot I_0 \][/tex]
Thus, this recursive system, with its initial condition, completely describes the explicit form of the function [tex]\( I(t) \)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.